THE INFLUENCE OF THE ADDITION OF RICE HUSK ADDITIVES AND MATOS TO THE VALUE OF CBR (CALIFORNIA BEARING RATIO) OF CLAY SOIL IN TERMS OF CURING TIME - Sampurna, Sindu Abadi; Iswan, Iswan; Zakaria, Ahmad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Soils have different types and different carrying capacity. One of them is clay soil that has the low carrying capacity. Viewed from the rapid development of infrastructure in Indonesia, does not rule out the possibility that the infrastructure built in areas with clay soil types. Given the small carrying capacity of the clay, the soil should be improved in order to support the development of a construction.soil improvement with an additional mixture of rice husk ash and matos as stabilizer can improve soil quality. This research was conducted with rice husk ash mixture of 6%, 8%, 10%, and 12% and matos with level 3,3898% gr. Then, curing for 7 days, 14 days, 21 days, and 28 days without immersion. Soil that used in research is from Sidomulyo, South Lampung is a type of clay soil that belongs to the A-7-5 group based on the AASTHO classification. Research in laboratory showed that 28 days of curing with 12% rice husk ash mixture had the highest CBR value from other curing durations. Soil clay CBR value increased from 7.3% to 31.8%. This shows that the ash mixture of rice husk and matos is quite effective in increasing the carrying capacity of clay soil. Keywords : Matos, CBR, Rice Husk Ash